Acute cold stress: a potential threat to Royle’s pika (Ochotona roylii) survival at Central Himalayas of Nepal - Koju, N. P.; Chalise, M. K.; Kyes, R. C. (Banko Janakari, 2021)
Climate change and its threat to human life and biodiversity are under discussion as the major issue of this century. In this study, pika (Ochotona roylii) was taken as a model animal to study the effect of changing climatic parameters in the Central Himalayas of Nepal. The study was carried out for three consecutive years (2011−2013) in the Kyanjing Valley situated at 3900 m asl, Langtang National Park, Nepal. The study focused on the population density of pika, its lowest elevation distribution, and temperature patterns of the pika-burrows and their immediate surroundings. An iButtons Temperature Recorder was installed inside a pika-burrow for acquiring burrow temperature while the ambient temperature data were obtained from the nearby metrological station. The population density of pika decreased compared to those based on the previous studies. Over the last 25 years, there was a significant increase in the minimum temperature (R2 =0.77) that decreased the snow cover which might have reduced the insulation effect and colder winter to animals living inside the burrow. The temperature inside the burrow was recorded below −5°C for nearly 50% time during January alone and 25% time during total winter days. The environment with a temperature below −5°C could be a threat to the survival of pikas suffering from acute cold stress. Neither there was any record of heat stress (above 25°C) recorded nor there was an increasing trend of the ambient maximum temperature within the LNP during the study period. The lowest elevation of the pika's habitat was found to have shifted 200 m upwards over the last 46 years, indicating that the animals had either migrated upwards or facing extinction locally at lower elevations. However, this short-term study is not sufficient to reflect the effects of climate change on the population of pika in the Central Himalayas. Therefore, a long-term study is required to explore the relation between pikas and their vulnerability to the changing climate